2015
DOI: 10.1007/s10854-015-3328-1
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis, characterization and optical properties of cobalt and lanthanide doped CdS nanoparticles

Abstract: Cadmium sulphide (CdS) nanoparticles doped with Co 2? and co-doped with Co 2? and rare earth metallic ions have been prepared by co-precipitation method. The synthesized nanoparticles have been characterized by X-ray powder diffraction studies, energy dispersive X-ray analysis, scanning electron microscopy (SEM), transmission electron microscopy (TEM), UV-visible spectroscopy, particle size by dynamic light scattering and photoluminescence studies. The X-ray diffraction results indicate that CdS nanoparticles … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(5 citation statements)
references
References 49 publications
0
5
0
Order By: Relevance
“…5b, it is found that the band gap energy ( E g ) for pure ZnO NPs is around 3.36 eV and decreases with Mg dopant (3.36 to 3.04 eV). The band gap is decreased due to strong quantum confinements and enhancement in their surface area to volume ratio [49]. Enhancement of redshift and decrease in band gap energy ( E g ) confirm the presence of Mg 2+ inside the Zn 2+ site of the ZnO lattice.…”
Section: Resultsmentioning
confidence: 99%
“…5b, it is found that the band gap energy ( E g ) for pure ZnO NPs is around 3.36 eV and decreases with Mg dopant (3.36 to 3.04 eV). The band gap is decreased due to strong quantum confinements and enhancement in their surface area to volume ratio [49]. Enhancement of redshift and decrease in band gap energy ( E g ) confirm the presence of Mg 2+ inside the Zn 2+ site of the ZnO lattice.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, a variety of lanthanide ions, including Nd 3+ , Sm 3+ , Eu 3+ , Tb 3+ , Gd 3+ , Er 3+ , and Yb 3+ , have been successfully doped into CdS QDs. [15][16][17][18][19][20] Compared to the transition-metal ions, lanthanide ions are advantageous dopants because of their sharper emission signals with a unique spectroscopic signature for unambiguous spectral identication. Therein, the Eu 3+ doping was demonstrated to be an effective way to enhance the performance of QDs in the photocatalysis and biomedical applications (immunoassay, detection of metal ions and imaging applications) as the edge over QDs, long uorescence lifetime, sharp emission peaks with narrow band width, and lack of blinking and biocompatibility.…”
Section: Introductionmentioning
confidence: 99%
“…When combined with doping, this enhanced mobility facilitates the diffusion of dopant atoms into the CdS lattice. This, in turn, can promote grain boundary migration and Ostwald ripening, wherein smaller grains dissolve and contribute to the growth of larger grains, leading to an increase in average grain size …”
Section: Resultsmentioning
confidence: 99%
“…This, in turn, can promote grain boundary migration and Ostwald ripening, wherein smaller grains dissolve and contribute to the growth of larger grains, leading to an increase in average grain size. 50 3.2. FTIR Spectroscopy Analysis.…”
Section: Structural Analysismentioning
confidence: 99%